1989
DOI: 10.1016/0022-3956(89)90028-9
|View full text |Cite
|
Sign up to set email alerts
|

DSM-III-R schizotypal personality traits in offspring of schizophrenic disorder, affective disorder, and normal control parents

Abstract: SummaryThe aggregation of disorder in families identified by a schizophrenic disorder proband (index case) has provided indirect clues to the question of diagnostic boundaries of schizophrenic spectrum categories. The Danish Adoption Studies provided quasi-experimental evidence for the range of expression of a putative schizophrenic spectrum disorder which was subsequently denoted schizotypal personality disorder (STPD) in DSM-III-R. It has been hypothesized that such schizophrenic spectrum categories bear a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
2
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 26 publications
2
43
2
1
Order By: Relevance
“…19 Suspiciousness and avoidant symptoms were explicitly examined in only two studies. 18,20 Suspiciousness was substantially more common in relatives of schizophrenic probands in both, reaching sta¬ tistical significance in one18 and at the trend level in the other.20 In one study,20 the avoidant symptoms ofsocial isolation and social anxiety did not distinguish relatives of schizophrenic and control probands. In the other,18 social isolation was significantly more common in relatives of schizophrenic probands, while social anxiety was not.…”
Section: Univariate Analysesmentioning
confidence: 93%
See 1 more Smart Citation
“…19 Suspiciousness and avoidant symptoms were explicitly examined in only two studies. 18,20 Suspiciousness was substantially more common in relatives of schizophrenic probands in both, reaching sta¬ tistical significance in one18 and at the trend level in the other.20 In one study,20 the avoidant symptoms ofsocial isolation and social anxiety did not distinguish relatives of schizophrenic and control probands. In the other,18 social isolation was significantly more common in relatives of schizophrenic probands, while social anxiety was not.…”
Section: Univariate Analysesmentioning
confidence: 93%
“…"2 ' Both studies that specifically ex¬ amined odd speech found that it was significantly more com¬ mon in the relatives of schizophrenic vs control probands. 18,20 Only one study specifically examined "social adaptation" and found it to be one of the most powerful discriminators of their borderline schizophrenic cases. 19 Suspiciousness and avoidant symptoms were explicitly examined in only two studies.…”
Section: Univariate Analysesmentioning
confidence: 99%
“…They are defined as increased sleep latency, frequent night waking, shorter sleep duration, and other parasomnias (2). Additionally, studies have found that schizotypal traits are present in people without schizophrenia, including offspring with parental psychiatric disorders and the general population (3). Schizotypal traits are of interest and importance in their own right but also have theoretical and clinical relevance to schizophrenia (4).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some studies indicate that schizotypy may be more common in biological relatives of individuals with schizophrenia than in other non-psychiatric samples (Kendler et al, 1995;Kremen et al, 1998), though it should be noted that some studies comparing the rates of schizotypal traits in relatives of patients with schizophrenia and in relatives of patients with affective psychoses have not confirmed the specificity of schizotypy to schizophrenia (Coryell and Zimmerman, 1989;Gilvarry et al, 2001;Mata et al, 2003;Squires-Wheeler et al, 1988;Squires-Wheeler et al, 1989). Although interview-based instruments are occasionally used, the measurement of schizotypy usually relies on at least one of many self-report inventories.…”
Section: Introductionmentioning
confidence: 99%